2021
DOI: 10.1016/j.isci.2021.102836
|View full text |Cite
|
Sign up to set email alerts
|

Gata2 heterozygous mutant mice exhibit reduced inflammatory responses and impaired bacterial clearance

Abstract: Summary Infectious diseases continually pose global medical challenges. The transcription factor GATA2 establishes gene networks and defines cellular identity in hematopoietic stem/progenitor cells and in progeny committed to specific lineages. GATA2-haploinsufficient patients exhibit a spectrum of immunodeficiencies associated with bacterial, viral, and fungal infections. Despite accumulating clinical knowledge of the consequences of GATA2 haploinsufficiency in humans, it is unclear how GATA2 haplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…We previously reported that a cohort of peritoneal cytokines was decreased in LPS-treated Gata2 heterozygous mutant mice ( Takai et al., 2021 ). Notably, many of the gene loci of these cytokines, including Il4 , Il13 , and Tnf , were enriched in the 646 GATA2 binding enhancer peaks.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that a cohort of peritoneal cytokines was decreased in LPS-treated Gata2 heterozygous mutant mice ( Takai et al., 2021 ). Notably, many of the gene loci of these cytokines, including Il4 , Il13 , and Tnf , were enriched in the 646 GATA2 binding enhancer peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Our ChIP data showed that GATA2 and PU.1 robustly bound to the -39 kb region, which suggests that the regulatory activity of the -39 kb region relies on GATA2 and PU.1. PU.1 is abundantly expressed in macrophages, whereas GATA2 levels are much lower in macrophages than in mast cells ( Takai et al., 2021 ). GATA2-deficient yolk sac progenitors still give rise to macrophages, which supports that GATA2 is dispensable for macrophage development ( Kaimakis et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations